SOCIAL COMMERCE MEDIA SOSIAL TIKTOK PENGARUHNYA TERHADAP KEPUTUSAN PEMBELIAN PADA PERUSAHAAN MNDY FOOTWEAR - Rajab, Ajay Muhamad; Gugum Gumilang Wirakanda (Jurnal Manajemen dan Pemasaran, 2024)
This study aims to analyze the influence of social commerce on the TikTok social media platform on purchasing decisions for MNDY Footwear products. Along with the increasing use of social media and e-commerce, social commerce has become an important trend in the digital business world. Using a quantitative approach, data was collected through questionnaires distributed to MNDY Footwear consumers active on TikTok. Regression analysis was used to test hypotheses and measure the influence of social commerce on purchasing decisions. The results show that social commerce on TikTok significantly influences purchasing decisions for MNDY Footwear products. Factors such as consumer interaction with review content and testimonials from other users, as well as other interactive features on TikTok, play an important role in influencing consumers' decisions to buy products. Social commerce contributes 43.9%.